Failure to experimentally infect 10 days-old piglets with a cell culture-propagated infectious stock of a classical genotype 1a porcine epidemic diarrhea virus - Gerber, Priscilla F.; Cao, Dianjun; Xiao, Chao-Ting; Chen, Qi; Lager, Kelly; Bosch, Berend Jan; Meng, Xiang-Jin; Halbur, Patrick G.; Opriessnig, Tanja (Frontiers in Veterinary Science, 2023)
Abstract: Introduction: Porcine epidemic diarrhea virus (PEDV) causes enteric disease in pigs of all ages. PEDV can be grouped into G1 (classical strains) and G2 (variant strains) based on sequence differences in the spike gene. Although several pathogenesis studies using contemporary strains of PEDV have been conducted to date, there is limited information on the pathogenesis of historical PEDV strains in contemporary pigs. This study aimed to investigate the clinical disease course of 10-day-old pigs infected with a classical European G1a PEDV strain from the 1980s which was last passaged in pigs in 1994. Methods: Sequencing results confirmed that the virus inoculum was a PEDV strain closely related to the prototype CV777 strain. The PEDV stock was serially passaged three times in Vero cells, and the P3 infectious virus stock was used to inoculate the pigs. A total of 40 pigs were inoculated using the oral route. Results: Pigs showed no enteric disease signs, and PEDV shedding was not detected for 44 days post-inoculation (dpi). At necropsy at 3 (5 pigs) or 7 dpi (5 pigs), no lesions were observed in intestinal sections, which were negative for PEDV antigen by immunohistochemistry. In addition, no IgG or IgA PEDV-specific antibodies in serum or fecal samples for 35 dpi further indicates a lack of infection. Titration of the leftover thawed and refrozen PEDV virus stock inoculum showed that the virus stock retained its infectivity in Vero cell culture and the porcine small intestine enterocytes cell line IPEC-J2. Discussion: The reasons for the loss of infectivity in pigs are unknown. In conclusion, we showed that a classical G1a PEDV strain successfully propagated in cell cultures could not orally infect 40 piglets.